Application of holographic imaging combined with real-time ultrasound-guided robot-assisted partial nephrectomy in the treatment of completely endophytic renal tumours: a retrospective cohort study comparing with pure laparoscopic surgery - Gao, Tongbin; Gao, Yuan; Wang, Dawei; Yu, Yongchun; Zhang, Zhentao; Tang, Feihu (Frontiers in Oncology, 2025)
BackgroundTo compare the perioperative outcomes and renal function preservation between holographic imaging combined with real-time ultrasound-guided robotic-assisted partial nephrectomy (RAPN) using the Da Vinci system and conventional laparoscopic partial nephrectomy (LPN) for completely endophytic renal tumours, and to explore the clinical advantages of novel imaging technologies.MethodsA single-centre retrospective cohort study was conducted, including 61 patients with completely endophytic renal tumours treated at Weifang People’s Hospital from January 2022 to January 2025. All patients underwent holographic imaging and intraoperative ultrasound. They were divided into the RAPN group (n=31) and the LPN group (n=30), with balanced baseline characteristics (all P>0.05), Crucially, all patients in both groups underwent preoperative holographic imaging and intraoperative ultrasound. Primary outcomes included warm ischemia time (WIT), intraoperative blood loss, operative time, and postoperative estimated glomerular filtration rate (eGFR) changes. Secondary outcomes comprised positive surgical margin rates, complications, and oncologic outcomes.ResultsPerioperative outcomes: WIT was reduced by 20% in the RAPN group (20 [IQR 20-25] vs. 25 [20-30] min, P = 0.037). Intraoperative blood loss distribution differed significantly (50 [20-50] vs. 50 [50-50] ml, P = 0.028), with 25% of RAPN cases achieving blood loss ≤20 ml (minimum in LPN: 50 ml). No statistical differences were observed in operative time (145 [126-193] vs. 133 [115-163] min) or hospital stay (7 [6-7] vs. 7 [5-7] days, both P>0.05). Complication rates were similar (9.7% vs. 6.7%, P=1.000). Renal function preservation: Postoperative eGFR on day 1 (84.67 ± 22.25 vs. 87.26 ± 19.92 ml/min, P=0.634) and at 3 months (92.17 ± 30.42 vs. 95.21 ± 22.91 ml/min, P=0.738) showed no significant differences. Oncologic safety: Both groups achieved 100% negative surgical margins, with a comparable distribution of malignant pathological subtypes and WHO/ISUP grades. No recurrence was detected during follow-up.ConclusionThe RAPN platform, when integrated with holographic imaging and real-time ultrasound guidance, demonstrates significant advantages in treating completely endophytic renal tumour. This integrated robotic approach offers a precise and minimally invasive solution for complex cases. Study limitations include its retrospective design, and a phase III RCT (N≥200) is recommended to validate long-term outcomes.